Pengaruh Kualitas Layanan, Prosedur Kredit Dan Promosi Terhadap Keputusan Umkm Melakukan Pinjaman Kredit Pada Lembaga Keuangan Bukan Bank (LKBB) Di Kecamatan Buleleng - Cahyadi, Made Andre; Diatmika, I Putu Gede (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine the effect of service quality, credit procedures and promotions on the decision of Mikro Small and Medium Enterprises to make credit loans to non-bank financial institutions in Buleleng sub-district. This research is a quantitative research. The population in this study were formal Mikro Small and Medium Enterprises actors in Buleleng District who were registered at the Department of Industry, Trade, Cooperatives and Mikro Small and Medium Enterprises in Buleleng Regency as many as 115 Mikro Small and Medium Enterprises. The number of samples used in this study was 53 samples using the Slovin formula and the sampling technique used was random sampling. The data used in this study are primary data obtained from distributing questionnaires. Data analysis used multiple linear regression analysis. The results of this study indicate that (1) service quality has a positive and significant effect on the decision to take credit, (2) credit procedures have a positive and significant effect on the decision to take credit, (3) promotion has a positive and significant effect on the decision to take credit.Â Â